The Adjustment of NATO's Space Policy and Its Implications - He Qisong (中国国际问题研究, 2024)
Under the US leadership, NATO has been adjusting its space policy and strengthening its space deterrence capabilities to address the so-called "threat" from China and Russia. While the deterrent effect of NATO's space policy remains to be seen, the various measures taken to implement the policy will have a considerable impact on the global space landscape, accelerating the weaponization of space and making it more difficult to prevent an arms race in space and govern space security.